Ummi Method: Al-Qur’an Innovation the Young Generation - Nurhikmah, Nurhikmah (Abjad Journal of Humanities & Education, 2024)
Ummi's method is a new innovation in helping the younger generation learn the Koran correctly. This method offers a holistic approach that includes tajwid, tahsin, and understanding the meaning of the Koran, with the aim of improving the quality of reading and understanding of the younger generation of the holy book. The Ummi method makes the teaching and learning process more interesting and relevant for children and teenagers. The type of research for this article is descriptive qualitative research (library research), data collection techniques using documentation by collecting various literature that can support the material for this article. Data analysis techniques use data reduction, presentation and drawing conclusions. Research and application of the Ummi Method shows that this approach can increase interest and skills in reading the Koran among the younger generation, as well as build a strong foundation for their spiritual and moral development. In conclusion, the Ummi Method offers a comprehensive and innovative solution to the challenges of learning the Qur'an in modern times, and has the potential to provide a significant positive impact for individuals and communities.